EFEKTIVITAS IKLAN DIGITAL GOOGLE ADSENSE - Alvita Tyas Dwi Aryani (Fakultas Ekonomi Universitas Pekalongan, 2017)
This study aimed to test the effectiveness of Google AdSense ads on your blog page using Google Chrome and Firefox browser. Adsense display is said to be effective if AdSense ads is able to display a product that has previously been seen on the Lazada web page. Using the experimental approach, this study concluded that effective AdSense looks good when viewed using Chrome or Firefox which in Chrome, users must sign in o rder to display AdSense effectively while in Firefox it does not require such procedures. Keywords: Efektivitas Tampilan Iklan Digital, AdSense, Chrome, Firefox, Lazada